2010
DOI: 10.1167/iovs.10-5456
|View full text |Cite
|
Sign up to set email alerts
|

Risk Factors for Corneal Infiltrative Events during Continuous Wear of Silicone Hydrogel Contact Lenses

Abstract: Corneal staining is common during continuous wear of SH lenses, but it is not associated with the development of a CIE. Smoking and substantial lens bacterial bioburden pose prominent risks of a CIE. In this study, more than 70% of the total risk of CIE in those with substantial lens bioburden is attributable to this exposure. (ClinicalTrials.gov number, NCT00727402).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
64
0
2

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 84 publications
(68 citation statements)
references
References 75 publications
2
64
0
2
Order By: Relevance
“…44 Whether melimine-coated lenses would be associated with inflammation because of the SICS-like response cannot be ruled out and needs further exploration. However, Szczotka-Flynn et al 45 showed that corneal staining is frequent during continuous contact lens wear and not associated with the development of corneal infiltrative events. This was a contradictory finding with the previous work by the same investigators 46 and was a consequence of fluorescein staining grades Bacterial adhesion to worn melimine-coated and control contact lenses.…”
Section: Discussionmentioning
confidence: 99%
“…44 Whether melimine-coated lenses would be associated with inflammation because of the SICS-like response cannot be ruled out and needs further exploration. However, Szczotka-Flynn et al 45 showed that corneal staining is frequent during continuous contact lens wear and not associated with the development of corneal infiltrative events. This was a contradictory finding with the previous work by the same investigators 46 and was a consequence of fluorescein staining grades Bacterial adhesion to worn melimine-coated and control contact lenses.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Although factors including longer wearing times for silicone hydrogel lenses during extended wear and patient characteristics such as new adopters or problem solver prescribing may be likely contributors, a recent study evaluating the risk factors for CIE during silicone hydrogel lens wear identified substantial lens bioburden as a significant causative factor (8.66 hazard ratio) with PA identified as a frequent contributor to these adverse lens-related events. 15 Biofilms are bacterial aggregates enclosed in an extracellular matrix that confer protection, allowing organisms to thrive under adverse conditions. 16 In animal models of infection, extended contact lens wear with concurrent bacterial challenge has been shown to result in significant neutrophil accumulation and biofilm formation on posterior lens surfaces.…”
mentioning
confidence: 99%
“…Lenses that cover the cornea, inadequate oxygen transmissibility of the lens, a relatively immobile fitting, poor tear exchange, and lens surface contamination may combine to influence these complications. 10 Szczotka-Flynn et al 11 have reported on clinical predictive factors for corneal infiltrates with extended wear (EW) of a silicone hydrogel lens. Smoking and bacterial contamination of lenses were associated with corneal infiltrate response (CIE), and more than 70% of the total risk of CIE in those with substantial lens bioburden is attributable to this exposure.…”
mentioning
confidence: 99%
“…Smoking and bacterial contamination of lenses were associated with corneal infiltrate response (CIE), and more than 70% of the total risk of CIE in those with substantial lens bioburden is attributable to this exposure. 11 Bacterial contamination of hydrogel contact lenses during asymptomatic wear may occur at a rate of approximately 50%, but this generally involves a small number of microorganisms. [12][13][14] Generally, coagulase negative staphylococci followed by S. aureus, streptococci and less frequently gram-negative bacteria are isolated from contact lenses or ocular surfaces after asymptomatic wear.…”
mentioning
confidence: 99%